PENENTUAN TINGKAT KEBISINGAN PADA PABRIK KELAPA SAWIT PT TASMA PUJA KECAMATAN KAMPAR TIMUR - Jasmareni Sri Kurniati Baalijas; Juandi '; Sugianto ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
The noise levels generated by the palm oil processing machine are demonstrated. Noise level measurement was done at different positions in the engine room area (location 1) and the office area (location 2) by using a Sound Level Meter (SLM) SL 4112. The results showed that the intensity of the noise caused by the engine plant in location 1produce the maximum value of 93.68 dB on Wednesday and 91.99 dB minimum value on Monday, while the second location has maximum value is 71.72 dB on Saturday and the minimum value is 68,63 dB on Monday for duration one week. This difference is due to the accumulation of noise levels with increasing time and background activities that can affect the value of the measurement. Measurements were carried out during one week on the average value of 93.68 dB at location 1 and 71.72 dB at location 2.